Somatic Modulation in Tinnitus: Clinical Characteristics and Treatment Outcomes - Lee, Ho Yun (J Int Adv Otol, 2020)
OBJECTIVES: We aimed to evaluate the clinical significance of the somatic modulation test in patients with tinnitus and analyze the treatment outcomes. MATERIALS AND METHODS: Medical records of patients who visited the tinnitus clinic at a local university hospital between October 2018 and April 2019 were retrospectively reviewed. RESULTS: The data of 81 patients were analyzed for this study, of which 61.7% (n=51) showed tinnitus modulation after one or more neck or jaw maneuvers. Patients with narrow-band noise tinnitus tended to show maneuver-induced modulation more frequently than those with pure-tone tinnitus (85.7% vs. 53.3%, p=0.010). Neck maneuvers reduced tinnitus loudness in 29.6% of the patients, while 27.2% of patients (n=22) reported worsening of tinnitus loudness, and 23.5% of patients (n=19) reported tinnitus suppression after jaw maneuvers. None of the patients with noise exposure history reported tinnitus modulation. Backward regression analysis revealed that age was an independent risk factor for improvement (Exp [B]=0.703, p=0.034, 95% CI=0.508–0.974). However, somatic modulation or medical treatments targeting somatic modulation were not related to improvement. CONCLUSION: Patients showing modulation after neck or jaw maneuvers have specific clinical characteristics. However, somatic modulation itself does not affect the final treatment outcome.